Transporte eletrônico em estruturas híbridas: uma aproximação usando funções de green de não-equílibrio - Facio, Thais Josiani Silva [UNESP] (2016)
In this work is proposed the theorical investigation of a double-path junction formed by a ferromagnetic and a supercondutor lead. The first path connects superconductor and ferromagnet by an insulator barrier while in the second path these metals are connected by a single level quantum dot. We have used the nonequilibrium Green’s functions to perform the calculations as well as to obtain the curves for electrical current, occupation numbers and transmittance. It is shown that the spin within the quantum dot can be manipulated by means of external parameters which can be of interesed in quantum computation applications.